Pentadbiran harta menurut Islam.. - Institut Kefahaman Islam, Malaysia (Kuala Lumpur: Institut Kefahaman Islam, Malaysia, 1999)
Wealth and property according to Islamic law in Malaysia; papers of a seminar.
Includes bibliographical references (p. 282-284).
Keywords: Property -- -- Malaysia; Property (Islamic law) -- -- Malaysia; Wealth -- -- Malaysia; Wealth -- -- Religious aspects -- -- Islam